Chapter 9 From Equal Citizens to Unequal Groups The Post-Yugoslav Citizenship Regimes - Štiks, Igor (Bloomsbury Academic, 2015)
ifferent citizens from other former Yugoslav republics who were permanent residents on their territory when the new citizenship regime came into effect. In their extreme manifestation, citizenship laws and practices have also been used as a subtle, but nonetheless powerful tool for ethnic cleansing. The deprivation of citizenship, and the subsequent loss of basic social and economic rights, has been quite effective in forcing a sizable number of individuals to leave their habitual places of residence and move either to 'their' kin states or abroad. The break-up of Yugoslavia and the other two multinational federations meant that millions literally went to bed as full-fledged citizens and woke up as individuals with questionable status.